Murat Höyük Early Bronze Age III Ceramic Assessment - Özdemir, Ayşe; Bircan, Özlem Tütüncüler (Fırat University, 2024)
Murat Höyük is located in Murat Village, Solhan District, Bingöl Province, Turkey. In 2019, rescue excavations initiated by the Elazığ Museum of Archaeology and Ethnography under the auspices of the Ministry of Culture and Tourism were completed. This study evaluated Early Bronze Age ceramics unearthed during the rescue excavations at Murat Höyük. The earliest of the four cultural layers identified in the studies belongs to the Early Bronze Age, dated between 2500-2200 BC. The ETÇ III layer is represented by its architecture, small finds, and ceramics. The Early Bronze Age settlement consists of five structures arranged around a single courtyard. The Murat Höyük form typology consists of pots, bowls, cups, pitchers, goblets, spout vessels, trays, and jars. Investigations have revealed that the Murat Höyük settlement and finds exhibit Upper Euphrates Basin characteristics. The research aims to contribute to the understanding of the cultural formation in the basin and provide new contributions to the regional archaeology by investigating the Murat Höyük settlement, which is located in the Bingöl Province, an area that has not been adequately researched despite being one of the best-researched areas in the Upper Euphrates Basin

Murat Höyük, Bingöl İli, Solhan İlçesi, Murat Köyü’nde yer almaktadır. 2019 yılında, TC Kültür ve Turizm Bakanlığı, Elazığ Arkeoloji ve Etnografya Müzesi başkanlığında başlatılan kurtarma kazıları 2019 yılında tamamlanmıştır. Bu çalışmada, Murat Höyük’te yapılan kurtarma kazılarında ele geçen Erken Tunç Çağı’na ait seramikler değerlendirimiştir. Yapılan çalışmalarda tespit edilen dört kültür tabakasından en erkeni MÖ 2500-2200 arasına tarihlenen Erken Tunç Çağı’na aittir. ETÇ III tabakası mimari, küçük buluntuları ve seramikleri ile temsil edilmektedir. Erken Tunç Çağı’na ait tek avlu çevresinde beş mekândan oluşan yapılaşma bulunmaktadır. Murat Höyük form tipolojisini çömlek, çanak, bardak, maşrapa, kadeh, akıtacaklı kap, tepsi ve küpten oluşturmaktadır. Araştırmalarda, Murat Höyük yapılaşması ve buluntularının, Yukarı Fırat Havzası özellikleri gösterdiği tespit edilmiştir. Çalışma kapsamında bölge içerisinde en iyi araştırılan alanlardan olan Yukarı Fırat Havzası içerisinde bulunan ancak yeterli olarak araştırmanın yapılmadığı Bingöl İli’nde yer alan Murat Höyük yerleşimi çalışmaları ile havza içerisindeki kültürel yapılanmanın ortaya konması ve bölge arkeolojisine yeni katkılar sağlanması hedeflenmektedir.
MURAT HÖYÜK ERKEN TUNÇ ÇAĞI III SERAMİĞİNİN DEĞERLENDİRİLMESİ
Keywords: Archaeological Science; Arkeoloji Bilimi